2012
DOI: 10.1016/j.ksujds.2012.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the conventional method for establishing the posterior palatal seal

Abstract: Objective: Providing sufficient posterior palatal seal (PPS) of a maxillary denture is necessary for retention. This research was designed to estimate the arbitrary scraping method used for establishing the PPS.Methods and material: Eight complete edentulous patients were selected. They received conventional complete dentures by using a scraping method for establishing the PPS. The posterior retention of the maxillary dentures was measured, the postpalatal area for each patient was visually estimated, and smea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…14,18 Another study carried out by kyung, kim and jung in yonsei university. 7 Results of their study suggest that fovea palatinae could be reliable landmarks or reference points in locating vibrating line and posterior limit of the maxillary denture.…”
Section: Discussionmentioning
confidence: 99%
“…14,18 Another study carried out by kyung, kim and jung in yonsei university. 7 Results of their study suggest that fovea palatinae could be reliable landmarks or reference points in locating vibrating line and posterior limit of the maxillary denture.…”
Section: Discussionmentioning
confidence: 99%
“…14 This makes the fovea palatinae reliable landmarks in determining vibrating line. 14,18 Another study carried out by kyung, kim and jung in yonsei university. 7 Results of their study suggest that fovea palatinae could be reliable landmarks or reference points in locating vibrating line and posterior limit of the maxillary denture.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that the fovea palatinae are reliable to locate vibrating line for posterior limit of removeable complete denture, while other are considered it unreliable. [32][33][34] 16,36 Many studies showed that the fovea palatinae can be reliable anatomical structure which helps in locating the vibrating line and posterior palatal seal for posterior limitation of upper removable complete dentures. 37 Some studies showed that patients whom adequate palatal outline at hard & soft palate junction, broader will be the posterior palatal seal part.…”
Section: Introductionmentioning
confidence: 99%